Strategies for Strengthening Indonesia’s National Economy in Facing Tax Rate Increases - Hanip Hidayatullah (Yayasan Cerdas Pedia Indonesia, 2025)
The increase in the value-added tax (VAT) rate from 11% to 12% starting in January 2025 is part of tax reform efforts to boost State's revenues and support national development. This policy is projected to generate additional revenue of up to IDR 150 trillion annually, which can be allocated for infrastructure, education, healthcare, and poverty alleviation. However, it also poses challenges such as reduced consumer purchasing power, increased inflation, and pressure on micro, small, and medium enterprises (MSMEs). This study examines strategies to strengthen the national economy through a comprehensive approach, including tax incentives for MSMEs, subsidies for essential goods, reinforcement of social assistance programs, and budget management transparency. With proper mitigation measures and measured policies, the negative impacts of this policy can be minimized without compromising public welfare and economic stability.